PERLINDUNGAN HUKUM TERHADAP ANAK PELAKU TINDAK PIDANA PENCABULAN (IAIN Tulungagung, 2019)
Crimes with child offenders in Indonesia are increasingly alarming from time to time. One of the most frequent crimes committed by children and child victims is sexual violence. One of the triggers of the onset of sexual violence by children with child victims is the rise of porn sites on the internet which can be easily accessed by children through mobile phones. This study used normative juridical research method. In accordance with the type of normative juridical research, the data collected is secondary data. The secondary data collection is intended to gain a theoretical foundation by studying the rules, documents and books that are related to this issue, and the opinions of scholars (doctrine). The result of the research shows that the form of juridical legal protection is regulated in special legislation for children, namely Law Number 35 Year 2014, the amendment to Law Number 23 Year 2002 regarding to the Child Protection and the implementation of legal protection have not been implemented optimally since it still uses the legislation, the old invitation, namely Law Number 23 Year 2002 on Child Protection. While the inhibiting factors in its implementation include legal factors, law enforcement officers, facilities and supporting facilities, community factors and cultural factors.Keywords: Legal Protection, Criminal Act of Abuse, Child